FIRM VALUE DETERMINANTS OF MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Novietta, Liza; Nurmadi, Ruswan (Accounting and Business Journal, 2021)
The purpose of this research aimed to analyzed the effect of Profitability and Firm Size on Firm Value with Capital Structure as intervening variable. This research used secondary data, that were financial reports from manufacturing companies listed in Indonesia Stock Exchange (IDX) on the period of 2015-2019. The analysis method used was path analysis. Based on the results of this research showed that Profitability had significant effect to Capital Structure, Firm Size had significant effect to Capital Structure, Profitability had significant effect to Firm Value, Firm Size had significant effect to Firm Value, Capital Structure had significant effect to Firm Value, Capital Structure was able to mediate the relationship between Profitability on Firm Value, and Capital Structure was able to mediate the relationship between Firm Size on Firm Value in manufacturing companies listed in Indonesia Stock Exchange (IDX) on the period of 2015-2019.